(3GdEOGQI GdeGdjI (B:s (3GdCSS GdYdejI h GdJWHjbjI (B/s - (3GdYdj, CSYO MejOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3GdJYQja HGdGOGQI GdeGdjI h CgOGagG , GdbjeI GdRefjI ddfbhO , GdbhGFe GdeGdjI h GdJMdjd GdeGdj , GdJNWjW GdeGdj (B: (3GdehGRfI GdfbOjI , GdbhGFe GdeGdjI GdJbOjQjI , JMdjd GdJYGOd , GdQaY GdeGdj h GdQaY GdJTZjdj , GdeNGWQI h GdYGFO , ebOeI HGdGhQGb GdeGdjI h GdeMaXI GdGSJKeGQjI , GOGQI h Jbjje GdGSge , cdaI QCS GdeGd h SjGSI JhRjY GdGQHGM(B.s
(3eQGLY U(B.393 (3; edGMb U(B.395s
Keywords: (3GdEOGQI GdeGdjIs; (3GdJMdjd GdeGdjs; (3GdJNWjW GdeGdjs